ANALISIS PERLENGKAPAN KANTOR PADA DIVISI PELAYANAN DI PT XXX - Fadillah, Muhammad Irfan; Faslah, Roni; Suherdi, Suherdi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This article discusses office equipment in the service division of PT XXX. Adequate office equipment is required by employees. This can affect the performance of employees. The method used is a qualitative approach and case studies. The goal is to find out the condition of office equipment, the positive and negative impacts on employees in the PT.XXX service division. Based on the results of the discussion of the data above, it can be concluded that office supplies are tools used to assist in the process of office activities. The condition of office equipment in the service division at PT XXX is inadequate. This is indicated by the lack of available office stationery (ATK) and frequent computer errors. The problems above are things that can affect the work processes of employees.